Laser photoablation of renal pelvic tumours - Weber, Bryce; McCallum, Theresa J.; Tulip, John; Moore, Ronald B. (Canadian Urological Association Journal, 2013)
We evaluated the clinical effects of the Zeiss OPMILAS (Oberkochen, Germany) multi–yttrium–aluminum–garnet (YAG) laser in the treatment of renal pelvic tumours as an alternative to nephroureterectomy. Four patients with evidence of transitional cell carcinoma (TCC) in the renal pelvis and a previous history of TCC of the bladder or opposite renal pelvis were treated with the Zeiss OPMILASmulti-YAG laser. Three patients underwent a retrograde ureteroscopic approach and 1 patient required percutaneous resection. Two wave lengths were used:1060 nm continuous coagulative mode and 1440 nm pulsed ablative mode. The patients were followed for 12, 24, 76 and 84 months, respectively. Two patients showed no evidence of recurrence as determined by cystoscopy, retrograde pyelography and selective pelvic urine cytology. One patient experienced a recurrence of TCC requiring subsequent treatment. The ureteroscopic approach was associated with fewer complications and a more rapid recovery, compared with the percutaneous approach. All patients with solitary kidneys avoided dialysis.